Is there any need for emergency neuroimaging in children with first complex febrile seizure? - Hassanzadeh rad, Afagh; Tabrizi, Manijeh; Dadashzadeh, Peyman; Aminzadeh, Vahid (Iranian Journal of Child Neurology, 2020)
Objectives: The current study aimed to assess the need for emergency neuroimaging in children with first CFC. Materials and methods: This is an analytic cross-sectional study which was conducted on children aged 6 -60 months with first CFS. Data were gathered by a form which assess age, sex, radiology type, temperature, the duration of fever before convulsion, the duration and the frequency of convulsion, family history of febrile seizure. Data were reported by descriptive statistics (mean, standard deviation, frequency, and percent) and analyzed by Fisher Exact Test in SPSS version 19. Results: In this study, 111 patients with first CFC and mean age of 21.18±11.83 months enrolled. Regarding the type of CFC, results showed that the highest and lowest frequencies belonged to multiple and multiple focal prolonged FC, respectively. Upper respiratory infection was the most common diagnosis. 2 unimportant abnormal neuroimaging results were noted. Conclusion: In this study results showed that performing emergency neuroimaging in patients with first CFS was not mandatory in the absence of developmental disorders, abnormal neurologic examination, underlying neurological disorder, and head trauma. This result is more important in our country, according to the lack of access to neuroimaging modalities in many hospitals in our country and due to its irradiation risk in childhood and cost consuming.